Oxidative state is associated with migration distance, but not traits linked to flight energetics - Péter László Pap; Orsolya Vincze; Csongor I. Vágási (Journal of Avian Biology)
Flight can be highly energy demanding, but its efficiency depends largely on flight style, wing shape and wing loading, and a range of morphological and lifestyle adaptations that can modify the cost of sustained flight. Such behavioural and morphological adaptations can also influence the physiological costs associated with migration. For instance, during intense flight and catabolism of reserves, lipid damage induced by pro‐oxidants increases, and to keep oxidative physiological homeostasis under control, the antioxidant machinery can be upregulated. Studies on the oxidative physiology of endurance flight have produced contradictory results, making generalization difficult, especially because multispecies studies are missing. Therefore, to explore the oxidative cost of flight and migration, we used samples collected during the breeding season from 113 European bird species and explored the associations of measures of antioxidant capacity (total antioxidant status, uric acid and glutathione concentration) and oxidative damage of lipids (malondialdehyde) with variables reflecting flight energetics (year‐round or specifically during migration) using a phylogenetic framework. We found that none of the traits predicting year‐round flight energy expenditure (flight style, wing morphology and flight muscle morphology) explained any measures of oxidative state. Our results suggest that birds endure their everyday flight exercise without or with low oxidative cost. However, oxidative damage to lipids and one component of the endogenous antioxidant system (uric acid), measured after the end of spring migration on breeding adult birds, increased with migration distance. Our results suggest that migration could have oxidative consequences that might be carried over to subsequent life‐history stages (breeding).